Fabrication of Sub-Micro Thin Layer Structures using Cyclopentanone Mix Solution as a Modified SU-8 3050 - Nguyen, Quang Long; Nguyen, Thi Thai; Chu, Thi Xuan; Nguyen, Minh Hang; Pham, Duc Thanh; Mai, Anh Tuan (Old Journal, 2017)
The SU-8 3000 series have been formulated for improved adhesion to the substrate and reduced coating stress than SU-8 2000 series. It is being used to fabricate microstructures in the range of thickness from some up to several hundred micrometers. However, it is hard to fabricate the layer of the SU-8 3000 series at sub-micrometer thinness. In this paper, we propose a procedure to reduce the thickness of the SU-8 3050 thin film. By mixing the SU-8 3050 with Cyclopentanone (CP) with different volume ratios, we can control viscosity of the mixture. Therefore, the thickness of the fabricated photoresist layer at 2000 rpm spincoating can be from 540 nm to 5330 nm. The mixing procedures of SU-8 fabrication have been optimized in order to enhance the unity of the thin layer photoresist. Some other fabrication factors are also investigated.